You are on page 1of 7

Surds:

(i) The surd conjugate of a + b (or a + b) is a - b (or a - b) and conversely.


(ii) If a is rational, b is a surd and a + b (or, a - b) = 0 then a = 0 and b = 0.
(iii) If a and x are rational, b and y are surds and a + b = x + y then a = x and b = y.

Complex Numbers:
(i) The symbol z = (x, y) = x + iy where x, y are real and i = -1, is called a complex (or,
imaginary) quantity;x is called the real part and y, the imaginary part of the complex number z =
x + iy.
(ii) If z = x + iy then z = x - iy and conversely; here, z is the complex conjugate of z.
(iii) If z = x+ iy then
(a) mod. z (or, | z | or, | x + iy | ) = + (x + y) and
(b) amp. z (or, arg. z) = = tan1
y/x (- < ).
(iv) The modulus - amplitude form of a complex quantity z is
z = r (cos + i sin); here, r = | z | and = arg. z (- < <= ).
(v) | z | = | -z | = z z = (x + y).
(vi) If x + iy= 0 then x = 0 and y = 0(x,y are real).
(vii) If x + iy = p + iq then x = p and y = q(x, y, p and q all are real).
(viii) i = -1, i = -1, i = -i, and i = 1.
(ix) | z + z| | z | + | z |.
(x) | z z | = | z | | z |.
(xi) | z/z| = | z |/| z |.
(xii) (a) arg. (z z) = arg. z + arg. z + m

(b) arg. (z/z) = arg. z - arg. z + m where m = 0 or, 2 or, (- 2).


(xiii) If be the imaginary cube root of unity then = (- 1 + 3i) or, = (-1 - 3i)
(xiv) = 1 and 1 + + = 0

Variation:
(i) If x varies directly as y, we write x y or, x = ky where k is a constant of variation.
(ii) If x varies inversely as y, we write x 1/y or, x = m (1/y) where m is a constant of variation.
(iii) If x y when z is constant and x z when y is constant then x yz when both y and z vary.

Arithmetical Progression (A.P.):


(i) The general form of an A. P. is a, a + d, a + 2d, a + 3d,.....
where a is the first term and d, the common difference of the A.P.
(ii) The nth term of the above A.P. is t = a + (n - 1)d.
(iii) The sum of first n terns of the above A.P. is s = n/2 (a + l) = (No. of terms/2)[1st term + last
term] or, S = / [2a + (n - 1) d]
(iv) The arithmetic mean between two given numbers a and b is (a + b)/2.
(v) 1 + 2 + 3 + ...... + n = [n(n + 1)]/2.
(vi) 1 + 2 + 3 +. + n = [n(n+ 1)(2n+ 1)]/6.
(vii) 1 + 2 + 3 + . . . . + n = [{n(n + 1)}/2 ].

Geometrical Progression (G.P.) :

(i) The general form of a G.P. is a, ar, ar, ar, . . . . . where a is the first term and r, the common
ratio of the G.P.
(ii) The n th term of the above G.P. is t = a.rn1
.
(iii) The sum of first n terms of the above G.P. is S = a [(1 - r)/(1 r)] when -1 < r < 1
or, S = a [(r 1)/(r 1) ]when r > 1 or r < -1.
(iv) The geometric mean of two positive numbers a and b is (ab) or, -(ab).
(v) a + ar + ar + . = a/(1 r) where (-1 < r < 1).

Theory of Quadratic Equation :


ax + bx + c = 0 ... (1)
(i) Roots of the equation (1) are x = {-b (b 4ac)}/2a.
(ii) If and be the roots of the equation (1) then,
sum of its roots = + = - b/a = - (coefficient of x)/(coefficient of x );
and product of its roots = = c/a = (Constant term /(Coefficient of x).
(iii) The quadratic equation whose roots are and is
x - ( + )x + = 0
i.e. , x - (sum of the roots) x + product of the roots = 0.
(iv) The expression (b - 4ac) is called the discriminant of equation (1).
(v) If a, b, c are real and rational then the roots of equation (1) are
(a) real and distinct when b - 4ac > 0;
(b) real and equal when b - 4ac = 0;
(c) imaginary when b - 4ac < 0;

(d) rational when b- 4ac is a perfect square and


(e) irrational when b - 4ac is not a perfect square.
(vi) If + i be one root of equation (1) then its other root will be conjugate complex quantity i and conversely (a, b, c are real).
(vii) If + be one root of equation (1) then its other root will be conjugate irrational quantity
- (a, b, c are rational).

Permutation:
(i) n (or, n!) = n (n 1) (n 2) 321.
(ii) 0! = 1.
(iii) Number of permutations of n different things taken r ( n) at a time P = n!/(n - 1)! = n (n
1)(n - 2) (n - r + 1).
(iv) Number of permutations of n different things taken all at a time = P = n!.
(v) Number of permutations of n things taken all at a time in which p things are alike of a first
kind, q things are alike of a second kind, r things are alike of a third kind and the rest are all
different, is <span style='font-size: 50%'>!/
(vi) Number of permutations of n different things taken r at a time when each thing may be
repeated upto r times in any permutation, is n .

Combination:
(i) Number of combinations of n different things taken r at a time = Cr = n!r!(nr)!

(ii) P = r! C.
(iii) C = Cn = 1.

(iv) Cr = Cn - r.
(v) Cr + Cn - 1 = n+1Cr

(vi) If p q and Cp = Cq then p + q = n.


(vii) Cr/Cr - 1 = (n - r + 1)/r.
(viii) The total number of combinations of n different things taken any number at a time = C +
C + C + . + C = 2 1.
(ix) The total number of combinations of (p + q + r + . . . .) things of which p things are alike of a
first kind, q things are alike of a second kind r things are alike of a third kind and so on, taken
any number at a time is [(p + 1) (q + 1) (r + 1) . . . . ] - 1.

Binomial Theorem:
(i) Statement of Binomial Theorem : If n is a positive integer then
(a + x)n = an + nC1 an - 1 x + nC2 an - 2 x2 + .. + nCr an - r xr + .. + xn .. (1)
(ii) If n is not a positive integer then
(1 + x)n = 1 + nx + [n(n - 1)/2!] x2 + [n(n - 1)(n - 2)/3!] x3 + + [{n(n-1)(n-2)..
(n-r+1)}/r!] xr+ . (-1 < x < 1) .(2)
(iii) The general term of the expansion (1) is (r+ 1)th term
= tr + 1 = nCr an - r xr
(iv) The general term of the expansion (2) is (r + 1) th term
= tr + 1 = [{n(n - 1)(n - 2)....(n - r + l)}/r!] xr.
(v) There is one middle term is the expansion ( 1 ) when n is even and it is (n/2 + 1)th term ; the
expansion ( I ) will have two middle terms when n is odd and they are the {(n - 1)/2 + 1} th and
{(n - 1)/2 + 1} th terms.
(vi) (1 - x)-1 = 1 + x + x2 + x3 + ..
(vii) (1 + x)-1 = I - x + x2 - x3 + .
(viii) (1 - x)-2 = 1 + 2x + 3x2 + 4x3 + . . . . .

(ix) (1 + x)-2 = 1 - 2x + 3x2 - 4x3 + . . . . .

Logarithm:
(i) If ax = M then loga M = x and conversely.
(ii) loga 1 = 0.
(iii) loga a = 1.
(iv) a logam = M.
(v) loga MN = loga M + loga N.
(vi) loga (M/N) = loga M - loga N.
(vii) loga Mn = n loga M.
(viii) loga M = logb M x loga b.
(ix) logb a x 1oga b = 1.
(x) logb a = 1/logb a.
(xi) logb M = logb M/loga b.

Exponential Series:
(i) For all x, ex = 1 + x/1! + x2/2! + x3/3! + + xr/r! + .. .
(ii) e = 1 + 1/1! + 1/2! + 1/3! + .. .
(iii) 2 < e < 3; e = 2.718282 (correct to six decimal places).
(iv) ax = 1 + (loge a) x + [(loge a)2/2!] x2 + [(loge a)3/3!] x3 + .. .

Logarithmic Series:

(i) loge (1 + x) = x - x2/2 + x3/3 - (-1 < x 1).


(ii) loge (1 - x) = - x - x2/ 2 - x3/3 - .. (- 1 x < 1).
(iii) loge [(1 + x)/(1 - x)] = x + x3/3 + x5/5 + (-1 < x < 1).
(iv) loge 2 = 1 - 1/2 + 1/3 - 1/4 + .
(v) log10 m = loge m where = 1/loge 10 = 0.4342945 and m is a positive number.